Investigation of IV characteristic of semiconductor diode and resistor using keithley 2450 source meter operated by labview programming - Mustafa, Anjum (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2019.